Theodore H. Hittell, The General Laws of the State of California, from 1850 to 1864, Inclusive 261 (1872) - (:unkn) unknown (My University, 1864)
§ 1585 [§1]: Prohibited the concealed carrying of any dirk, pistol, sword cane, slungshot, or "other dangerous or deadly weapon." Exempted any peace officer or officer acting under the law of the United States. Punishable by imprisonment for 30-90 days or fine of $20-200.
Keywords: CARRY - CONCEALED